The kinetics of the apple cv. Granny Smith drying in laboratory conditions - Paunović, D., Poljoprivredni fakultet, Beograd - Zemun (Serbia); Zlatković, B., Poljoprivredni fakultet, Beograd - Zemun (Serbia); Mirković, D., Poljoprivredni fakultet, Beograd - Zemun (Serbia) (Voćarstvo (Serbia), 2011)
In the last decade on the world market there is a great interest in dried apple products (publicity-called apple chips). The subject of this paper is the kinetics of the apple cv Granny Smith drying in laboratory dehydrator with the idea of pinpointing at which level of humidity comes to achieving a maximum speed of evaporation and at which level of humidity apple slices are beginning to change in color and geometric shape. The experiment included two temperature regimes of drying, batch process (constant air temperature of 70 deg C for a period of 8h) and simulated continual process (the air temperature of 70 deg C for a period of 3 h and the air temperature of 50 deg C for a period of 5 h). The amount of evaporated water is expressed in relative and absolute units of measure. The purpose of this paper is to optimize the technological process of drying apple slices and in terms of oxidation of polyphenolic compounds to find an adequate temperature treatment which will provide that the final product contains no additives and to be technologically and organoleptically acceptable. The results showed that in simulated continual process of drying the lower maximum speed of drying is achieved, drying is more evenly and in this way the technological process is finished with a smaller temperature stress for plant tissue, resulting in a much better quality of the final product.